STUDI PRODUKSI ASAM LEVULINAT DARI PATI UBI GAJAH (Manihot esculenta) MENGGUNAKAN KATALIS ASAM SULFAT - Wisnu Aditya; Amir Awaluddin; Saryono ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The utilization of Manihot esculenta to produce platform chemical such as levulinic acid (LA) has been studied in detail to optimize the LA production. The LA production from Manihot esculenta was monitored using reaction times of the hidrolysis reaction (3-85 min.), the reaction temperatures (150˚C, 170˚C, and 190˚C), and concentrations of sulfuric acid as the catalyst (1%, 3%, and 5%). The products obtained were then characterized using high performance liquid chromatography (HPLC) to determine the contents of gl ucose, hydroxymethylfurfural (HMF) and LA. The result showed that the LA production increased with the rise of temperature and catalyst concentration, whereas the glucose and HMF production decreased with the rise of temperature and catalyst concentration. The highest production of LA reached approximately 50% (based on initial concentration of biomass) at reaction temperature of 170˚C and 5% of sulfuric acid concentration for 70 minutes of reaction time.